Glucocorticoid Receptor Maintains Vasopressin Responses in Kidney Collecting Duct Cells - Yang, Hsiu-Hui; Su, Shih-Han; Ho, Cheng-Hsuan; Yeh, Ai-Hsin; Lin, Yi-Jiun; Yu, Ming-Jiun (Frontiers in Physiology, 2022)
Water permeability of the kidney collecting ducts is regulated in part by the amount of the molecular water channel protein aquaporin-2 (AQP2), whose expression in turn is regulated by the pituitary peptide hormone vasopressin. We previously showed that stable glucocorticoid receptor knockdown diminished vasopressin-induced Aqp2 gene expression in the collecting duct cell model mpkCCD. Here, we investigated the pathways regulated by glucocorticoid receptor by comparing transcriptomes of the mpkCCD cells with or without stable glucocorticoid receptor knockdown. Glucocorticoid receptor knockdown down-regulated 5,394 transcripts associated with 55 KEGG pathways including “vasopressin-regulated water reabsorption”, indicative of positive regulatory roles of these pathways in vasopressin-induced Aqp2 gene expression. Quantitative RT-PCR confirmed down-regulation of the vasopressin V2 receptor transcript upon glucocorticoid receptor knockdown. Glucocorticoid receptor knockdown up-regulated 3,785 transcripts associated with 42 KEGG pathways including “TNF signaling pathway” and “TGFbeta signaling pathway”, suggesting negative regulatory roles of these pathways in vasopressin-induced Aqp2 gene expression. Quantitative RT-PCR confirmed up-regulation of TNF and TGFbeta receptor transcripts upon glucocorticoid receptor knockdown. TNF or TGFbeta inhibitor alone, in the absence of vasopressin, did not induce Aqp2 gene transcription. However, TNF or TGFbeta blunted vasopressin-induced Aqp2 gene expression. Specifically, TGFbeta reduced vasopressin-induced increases in Akt phosphorylation without inducing epithelia-mesenchymal transition or interfering with vasopressin-induced apical AQP2 trafficking. In summary, our RNA-seq transcriptomic comparison revealed positive and negative regulatory pathways maintained by glucocorticoid receptor for vasopressin-induced Aqp2 gene expression.